3(x-5)=7(x-9)

Simple and best practice solution for 3(x-5)=7(x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-5)=7(x-9) equation:



3(x-5)=7(x-9)
We move all terms to the left:
3(x-5)-(7(x-9))=0
We multiply parentheses
3x-(7(x-9))-15=0
We calculate terms in parentheses: -(7(x-9)), so:
7(x-9)
We multiply parentheses
7x-63
Back to the equation:
-(7x-63)
We get rid of parentheses
3x-7x+63-15=0
We add all the numbers together, and all the variables
-4x+48=0
We move all terms containing x to the left, all other terms to the right
-4x=-48
x=-48/-4
x=+12

See similar equations:

| 3(w-6)-3=-3(-5w+5)-3w | | 30-3x=16+11x | | (2x^2)-5=(3x^2)-12x+31 | | 113a=2 | | 4x+16=3x+18 | | 8(y-9)=-32 | | 1-x-1/2=1-(1/2x+3) | | (x-21)/7=1.8 | | 2(3y-8)=8 | | (21+x)*(21/x)=147 | | 4x+7=8+4x-1 | | 6x5+-9x2+12x=0 | | 3x+5=x-11+2x | | 1x+30=0 | | -3(1+8n)=-123 | | 3/2n-11/2=33/82 | | 3x-5=25+9x | | -3(x+1)+8x=4-x+5 | | x+7=12-x+13 | | 5v+9-2(-6v-2)=3(v-1) | | 8(8n-7)=136 | | x^2-46x+84=0 | | 3(b-4)=-3 | | 3h-4h+9=-1h+15 | | X+2x+(2x-3)=37 | | 4f+11=4 | | 5(m-4)=5m-8-3m | | 2m-3/3-4m-2/6=3 | | x+13/3=2x+1 | | 0.01(x-5)=30 | | 2(x–4)=6x+8 | | 50+85+x+56=180 |

Equations solver categories